Uncovering Community Structures in Inter-industry Labor Mobility Networks in Argentina - Semeshenko, Viktoriya (2023)
In this paper we systematically explore high granularity economic activity data of labor flows using a network filtering reduction technique, focusing on a meso-structure analysis of relevant groups of economic activities. Using administrative data of interindustry labor flows for 1996-2020, we built the networks, extracted their representative backbones and applied a community detection algorithm. The results unmask inter-industry connectivity with persistent structures and well-identified communities organized in a core-periphery structure.